2023
DOI: 10.1029/2022jb025745
|View full text |Cite
|
Sign up to set email alerts
|

A New P‐Wave Tomographic Model (CAP22) for North America: Implications for the Subduction and Cratonic Metasomatic Modification History of Western Canada and Alaska

Abstract: Our understanding of the present‐day state and evolution of the Canadian and Alaskan mantle is hindered by a lack of absolute P‐wavespeed constraints that provide complementary sensitivity to composition in conjunction with existing S‐wavespeed models. Consequently, cratonic modification, orogenic history of western North America and complexities within the Alaskan Proto‐Pacific subduction system remain enigmatic. One challenge concerns the difficulties in extracting absolute arrival‐time measurements from oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 190 publications
(499 reference statements)
1
9
0
Order By: Relevance
“…All results show elevated “410,” slightly depressed “660,” and thus thick MTZ in central Alaska (near 64°N, 150°W in Figure 6), suggesting that the Pacific slab has entered the MTZ in this region. This is consistent with recent tomography models (e.g., Boyce et al., 2023; Gou et al., 2019; Jiang et al., 2018; Martin‐Short et al., 2018). Furthermore, the results of applying the appropriate corrections based on the MS18 and J18 models exhibit little topography on the “660” (Van Stiphout et al., 2019) in central Alaska, indicating that the slab has probably not penetrated into the lower mantle.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…All results show elevated “410,” slightly depressed “660,” and thus thick MTZ in central Alaska (near 64°N, 150°W in Figure 6), suggesting that the Pacific slab has entered the MTZ in this region. This is consistent with recent tomography models (e.g., Boyce et al., 2023; Gou et al., 2019; Jiang et al., 2018; Martin‐Short et al., 2018). Furthermore, the results of applying the appropriate corrections based on the MS18 and J18 models exhibit little topography on the “660” (Van Stiphout et al., 2019) in central Alaska, indicating that the slab has probably not penetrated into the lower mantle.…”
Section: Discussionsupporting
confidence: 91%
“…(2017) and Boyce et al. (2023) found that the NE‐SW‐striking high‐velocity feature extends as deep as 600‐km depth, but the feature in the latter study is more concentrated in southwestern Alaska in the lower MTZ, whereas Gou et al. (2019) observed that the anomalies weaken significantly beyond 500‐km depth.…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations